The Role of Payment Tools Using Card to Stability of Sharia Banking Financial System - Syahrijal Hidayat; Endrianur Rahman Zain (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The financial system has a very strategic role in supporting economic activities. The financial system which is part of the economic system carries out an intermediary function that allocates funds from parties who experience excess funds (surpluses) to those who lack funds (deficit). Islamic financial system is a financial system that bridges between those who need funds and those who are excess funds through financial products and services that are in accordance with Islamic principles. The Development of Card Based Payment Instruments in Indonesia and the development of sharia banking in Indonesia experienced harmonious and positive growth from 2012 to 2020. If it is associated with the development of Card Based Payment Instruments that the author can conclude that the use of electronic cards such as credit cards, cards ATM and ATM debit cards have a very important and positive role for the development of sharia banking financial stability, namely sharia banking business activities because the use of electronic cards will further enhance sharia banking business activities, namely funding, lending, and services.